Comparative study of the effects of chlorinated polyethylene and acrylic impact modifier on the thermal degradation of poly(vinyl chloride) compounds and poly(vinyl chloride)/(oil palm empty fruit bunch) composites - Abu Bakar, Aznizam (Society of Plastics Engineers, 2010)
The effects of chlorinated polyethylene (CPE) and acrylic impact modifier (AIM) on the thermal degradation of poly(vinyl chloride) (PVC) compounds and composites were investigated. The amounts of AIM and CPE used were fixed at 9 parts per hundred parts of resin (phr), while oil palm empty fruit bunch (OPEFB) fiber content was increased from 0 to 40 phr. To produce composites, the PVC formulations were dry-blended by using a laboratory blender before being milled into sheets on a two-roll mill at 165°C. The milled sheets were then hot-pressed at 180°C. The thermal degradation of the specimens was evaluated by using thermogravimetry in a nitrogen environment. Thermal stability of the PVC/CPE compounds and PVC/CPE/OPEFB composites was improved by the addition of CPE. The CPE retarded the dehydrochlorination of PVC. However, the stabilization effect was reduced by the incorporation of OPEFB at levels of 30 and 40 phr. The presence of AIM accelerated the dehydrochlorination of PVC/AIM compounds and PVC/AIM/OPEFB composites.